Perinatal variables influencing cord blood thyroid stimulating hormone - Garg, Manasi D.; Kumar, Poornima; Abirami, Sakthi; M., Manikandan; Krishnan, Lalitha (International Journal of Contemporary Pediatrics, 2018)
Background: Newborn screening using cord blood Thyroid Stimulating Hormone (TSH) is an effective and an easy way to screen babies for congenital hypothyroidism. Congenital hypothyroidism is a common preventable and treatable cause of mental retardation. Early diagnosis with the help of newborn screening aids in timely management and decreased morbidity. Various maternal and neonatal variables can affect cord blood TSH level thereby affecting the accurate diagnosis of congenital hypothyroidism. This study aims at studying the perinatal variables affecting cord blood TSH. Methods: In a retrospective cross-sectional study conducted in a tertiary care hospital, the hospital case records of 1465 newborn and their mother were studied for variables including cord blood TSH, maternal age, mode of delivery, parity, gender of baby, gestational age and growth of baby. The effect of these perinatal variables on cord blood TSH was analysed statistically. P value below 0.05 was considered as statistically significant. The statistical analysis was done used the SPSS software version 18.0. Results: The median cord blood TSH was 8 microIU/ml (IQR= 6-12) with 8.1% newborns having values more than 20 microIU/ml. Cord blood TSH was significantly raised in male babies (p <0.01) and in neonates born by assisted vaginal delivery (p <0.01). Significant increase in cord blood TSH (p <0.02) was observed in neonates born to primiparous mothers. Maternal age, gestational age of the newborn and growth of the newborn did not have significant effect on cord blood TSH values. Conclusions: The mode of delivery, parity and gender of the baby were found to be significant variables affecting cord blood TSH values. Hence, cord blood TSH values should be interpreted in the light of these perinatal variables.